Epitope mapping of type VII collagen. Identification of discrete peptide sequences recognized by sera from patients with acquired epidermolysis bullosa. - Lapiere, J C (1993)
Epidermolysis bullosa acquisita (EBA) is an acquired blistering skin disease characterized by the presence of IgG autoantibodies that recognize type VII (anchoring fibril) collagen. In this study, we have mapped the antigenic epitopes within the type VII collagen alpha chain by Western immunoblotting analysis with sera from 19 patients with EBA, using bacterial collagenase- or pepsin-resistant portions of type VII collagen and a panel of 12 recombinant fusion proteins corresponding to approximately 80% of the primary sequence of the alpha 1 (VII) collagen polypeptide. These studies identified four major immunodominant epitopes localized within the amino-terminal, noncollagenous (NC-1) domain. In addition to EBA, sera from three patients with bullous systemic lupus erythematosus (BSLE) were tested. The pattern of epitopes recognized by these sera were similar to those noted with EBA, suggesting that the same epitopes could serve as autoantigens in both blistering conditions. In contrast, sera from healthy controls or from patients with unrelated blistering skin diseases did not react with type VII collagen epitopes. Collectively, the results indicate that the immunodominant epitopes in EBA and BSLE lie within the noncollagenous regions of type VII collagen. The precise role of the circulating autoantibodies in the pathogenesis of these blistering diseases remains to be elucidated. Conceivably, however, such antibodies could disrupt the assembly of type VII collagen into anchoring fibrils and/or interfere with their interactions with other extracellular matrix molecules within the cutaneous basement membrane zone.